Pancreatic schwannoma: A rare case and a brief literature review. (2016) - Ercan, Metin; Aziret, Mehmet; Bal, Ali; Şentürk, Adem; Karaman, Kerem; Kahyaoğlu, Zeynep; Koçer, Havva Belma; Bostancı, Birol; Akoğlu, Musa
Highlights: Pancreatic schwannoma is an extremely rare tumor. Pancreatic schwannoma was stained with S-100 and vimentin. The preoperative diagnosis of pancreatic schwannoma is an important in terms of choose surgery method. Surgical resection is a curative treatment method for pancreatic schwannoma. Abstract: Introduction: Pancreatic schwannoma (PS) is an extremly rare benign tumor. Less than 50 cases of pancreatic schwannoma have been described in the English literature over the past thirty years. Presentation of case report: A 63-year-old female underwent left modified radical mastectomy 2 years ago due to breast cancer. During her routine check-up, a 65 × 63 × 55 mm measured calcified, well-demarcated, cystic-mass having septations and calcifications that localized to the pancreatic head was detected by abdominal computerized tomography. She was asymptomatic and her tumor markers were in normal ranges. A standard Whipple procedure was performed, and the histo-pathological diagnosis of the resected specimen was reported as ancient schwannoma with clear surgical margins. Patient's postoperative course was eventful. She had a biliary leakage after surgery which was managed conservatively. She is under follow-up. Discussion: Pancreatic schwannoma also known as neurilemoma or neuroma is a slowly growing, encapsulated, mostly benign tumor with smooth well-delineated margins that originates from myelin producing schwann cells located on the nerve sheath of the peripheral epineurium of either the sympathetic or parasympathetic autonomic fibers. PS's are extremly rare. The head of pancreas being involved in the vast majority of cases (40%), followed by its body (20%). Management of pancreatic schwannomas remains largely controversial. Both enucleation and radical surgical resections have revealed great therapeutic efficiency. with a well prognosis without recurrences. Conclusion: Although rare, PS's should be considered in the differential diagnosis of the other solid or cystic masses of the pancreas.